How Can Behavioural Insights Be Used to Improve EU Policy? - Xavier Troussard; René van Bavel (Intereconomics, 2018)
The introduction of behavioural insights into policy-making is welcome, because they challenge traditional assumptions in policy-making which are largely inspired by neoclassical economic thinking. In line with good evidence-based policy-making, they make us question and test how people behave instead of assuming we already know the answer.
Keywords: 330